Seeking the unseen - Solomon, Mildred Z. (The Hastings Center report, 2012)
When Dan Callahan and Will Gaylin began The Hastings Center, they saw and sought to study the unseen. They were among the very first to recognize that remarkable advances in biomedical technology were generating questions our society had never before faced. As I take the helm of The Hastings Center forty-plus years later, it's now my job to be sure we see, name, grapple with, and act on today's questions. Over the next two years, the Center will engage its scholars, our Fellows, other bioethicists, scientists, social science and humanities scholars, health care policy-makers, and key stakeholders such as journalists, educators, and patients in defining today's set of critical questions.